Tinjauan Yuridis terhadap Perkawinan di Bawah Umur dalam Perspektif Undang-Undang Perkawinan di Indonesia - Taufik, Taufik; Winario, Mohd (Journal of Legal Sustainability, 2025)
This study aims to juridically analyze the practice of underage marriage in the perspective of Law Number 1 of 1974 on Marriage, as amended by Law Number 16 of 2019. The main focus of this research is to examine the conformity of such practices with positive legal provisions and their legal implications for child protection and human rights. The research method used is normative legal research, employing a statute approach and a conceptual approach. Data were obtained through literature studies on statutory regulations, court decisions, and relevant legal literature. The results of the study show that although the minimum age for marriage has been raised to 19 years for both males and females, underage marriage still occurs through the marriage dispensation mechanism. However, the implementation of this dispensation often raises legal and social issues due to weak oversight and the persistent influence of cultural and social pressures in several regions. Therefore, regulatory reinforcement and consistency in law enforcement are needed to ensure the protection of children and the fulfillment of their fundamental rights in the context of marriage.